Kelâm ilminde amellerin boşa çıkması sorunu - Çakar, Ferihan (My University, 2017)
Amellerin boşa çıkarılıp karşılıksız bırakılması mânâsını ifade eden ihbât konusu, temeli amel-iman münâsebetine dayanan ve Kur’ân-ı Kerîm’de dikkatli olunması yönünde uyarılarda bulunulan mühim bir husustur.

The matter of frustration which means the disconfirmation and the act of leaving one's deeds unreturned, is essentially based on the relation between iman and deeds, and is a significant issue that we are advised to be careful about in the Quran.
Keywords: Amel; Cezâ Quran; Deed; Frustration; Hadis; Hadith; Iman; İhbât; İman; İslam dini; Kelam; Kur’ân-ı Kerîm; Mükâfât; Punishment; Reward